Unilateral hippocampal sparing during whole brain radiotherapy for multiple brain metastases: narrative and critical review - Pospisil, Petr; Hynkova, Ludmila; Hnidakova, Lucie; Maistryszinova, Jana; Slampa, Pavel; Kazda, Tomas (Frontiers in Oncology, 2024)
Background: The landscape of brain metastases radiotherapy is evolving, with a shift away from whole-brain radiotherapy (WBRT) towards targeted stereotactic approaches aimed at preserving neurocognitive functions and maintaining overall quality of life. For patients with multiple metastases, especially in cases where targeted radiotherapy is no longer feasible due to widespread dissemination, the concept of hippocampal sparing radiotherapy (HA_WBRT) gains prominence.Methods: In this narrative review we explore the role of the hippocampi in memory formation and the implications of their postradiotherapy lateral damage. We also consider the potential advantages of selectively sparing one hippocampus during whole-brain radiotherapy (WBRT). Additionally, by systematic evaluation of relevant papers published on PubMed database over last 20 years, we provide a comprehensive overview of the various changes that can occur in the left or right hippocampus as a consequence of radiotherapy.Results: While it is important to note that various neurocognitive functions are interconnected throughout the brain, we can discern certain specialized roles of the hippocampi. The left hippocampus appears to play a predominant role in verbal memory, whereas the right hippocampus is associated more with visuospatial memory. Additionally, the anterior part of the hippocampus is more involved in episodic memory and emotional processing, while the posterior part is primarily responsible for spatial memory and pattern separation. Notably, a substantial body of evidence demonstrates a significant correlation between post-radiotherapy changes in the left hippocampus and subsequent cognitive decline in patients.In the context of individualized palliative radiotherapy, sparing the unilateral (specifically, the left, which is dominant in most individuals) hippocampus could expand the repertoire of strategies This is a provisional file, not the final typeset article available for adapted WBRT in cases involving multiple brain metastases where stereotactic radiotherapy is not a viable option. Prospective ongoing studies assessing various memory-sparing radiotherapy techniques will define new standard of radiotherapy care of patients with multiple brain metastases.